IMPLEMENTATION OF VALUE CHILD SOLIDARITY IN ISLAM AT THE MIDDLE-SECONDARY SCHOOL IN SUKAMAKMUR SUB DISTRICT - Aulia Rahmi; Fitriah Fitriah (Universitas Serambi Mekkah, 2017)
The value of solidarity is very meaningful for every society, especially children in school, becauseof the sense of solidarity will be established relationships that love each other, and need eachother. But the value of solidarity has begun to fade in junior high schools in Aceh, especially inschools in Sub District Sukamakmur since the development of technology. This research wasconducted in junior high school (SMP) and MTsN Sukamakmur sub district. In this sub districtthere is SMP Negeri 1 Unggul Sukamakmur and MTsN Jeurela. Researchers use data collectiontechniques namely, interviews, documentation and observation in data collection. The results ofresearch after the researchers to the field is the implementation of the value child solidarity inIslamic education in MTsN jeurela stronger than Implementation of the value child solidarity inIslamic education in SMP 1 unggul, It is because in MTsN there are many subjects of religionwhereas in junior high school (SMP) more general lesson. Lack of students' understanding of theimportance of brotherhood values or solidarity in life and environment that is less conducive is amajor factor in the weak implementation of the value child solidarity in Islamic education. Torealize the values child solidarity in Islamic education in junior high school (SMP) can be done invarious ways such as giving understanding to the students the benefits of solidarity in Islam, Cashcitation, quotation of donations to be distributed to the needy, responsibility to the daily picket,familiarize students work together and help each other in learning, etc.